Incorporating non-climate externalities receiving public attention in the optimisation of grid decarbonisation: the case of Ontario - Zhenglin Liu; I Daniel Posen; Bryan Karney (Environmental Research: Energy)
This paper extends a cost-optimising electricity capacity expansion model for the Canadian province of Ontario to incorporate several non-climate externalities, reflecting the way such externalities have been shown to impact the public acceptance of clean electricity policy. A Textometrica analysis of 225 news articles identified employment and health as the externalities receiving the most public attention, followed by land use and ecological impacts. Multiple sets of monetary valuations of the impact of different generation technologies on each externality were generated from the literature. The model was run with each combination of valuations incorporated into the cost function and with no externalities under both partial (carbon cost of $200 CAD/tonne) and full decarbonisation. Incorporating externalities was found to decrease optimal emissions by 21% on average across partial decarbonisation scenarios, and generally to increase optimal wind capacity expansion and retirement of gas generation (solar expansion and nuclear expansion were not optimal in any modelled scenario). Significantly, the incorporation of externalities only modestly increases the accounting cost of the system. All these impacts are much smaller in the case of full decarbonisation. Results are highly sensitive to the health impact valuations used and the presence of community support for wind expansion, which determines whether property values are impacted. Application of this modelling approach and these findings should not only reduce the social cost of electricity system decarbonisation measures but also facilitate their implementation by decreasing the risk of politicised opposition.